2016
DOI: 10.1155/2016/2864028
|View full text |Cite
|
Sign up to set email alerts
|

Determining the Surfactant Consistent with Concrete in order to Achieve the Maximum Possible Dispersion of Multiwalled Carbon Nanotubes in Keeping the Plain Concrete Properties

Abstract: A new surfactant combination compatible with concrete formulation is proposed to avoid unwanted air bubbles created during mixing process in the absence of a defoamer and to achieve the uniform and the maximum possible dispersion of multiwalled carbon nanotubes (MWCNTs) in water and subsequently in concrete. To achieve this goal, three steps have been defined: (1) concrete was made with different types and amount of surfactants containing a constant amount of MWCNTs (0.05 wt%) and the air bubbles were eliminat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 29 publications
0
17
0
Order By: Relevance
“…However, Azhari [110] claimed that methylcellulose could negatively affect the mechanical properties owing to the air-entraining effect. High level of SDS concentration could also lead to an increasing of air bubbles and a reduction on concrete mechanical properties [35,72,111]. Adresi, Hassani [111] suggested that the proportions would be 1:9, 1:12, 1:5 of a combination of SDS and superplasticizer, when making ordinary concrete, high compressive strength concrete, and requiring a large amount carbon nanotubes dispersed in aqueous phase, respectively.…”
Section: Surfactants and Admixturesmentioning
confidence: 99%
See 2 more Smart Citations
“…However, Azhari [110] claimed that methylcellulose could negatively affect the mechanical properties owing to the air-entraining effect. High level of SDS concentration could also lead to an increasing of air bubbles and a reduction on concrete mechanical properties [35,72,111]. Adresi, Hassani [111] suggested that the proportions would be 1:9, 1:12, 1:5 of a combination of SDS and superplasticizer, when making ordinary concrete, high compressive strength concrete, and requiring a large amount carbon nanotubes dispersed in aqueous phase, respectively.…”
Section: Surfactants and Admixturesmentioning
confidence: 99%
“…High level of SDS concentration could also lead to an increasing of air bubbles and a reduction on concrete mechanical properties [35,72,111]. Adresi, Hassani [111] suggested that the proportions would be 1:9, 1:12, 1:5 of a combination of SDS and superplasticizer, when making ordinary concrete, high compressive strength concrete, and requiring a large amount carbon nanotubes dispersed in aqueous phase, respectively. There was also other researches regarding the negative effect of surfactant.…”
Section: Surfactants and Admixturesmentioning
confidence: 99%
See 1 more Smart Citation
“…A very high degree of CNT dispersion and stable aqueous solution (stable for a few months) is obtained in the presence of SDS, which was investigated by UV spectroscopy and transmission electron microscopy (TEM) [ 27 ]. Some studies on the use of the CNT dispersion with SDS [ 32 , 33 , 34 ], NaDDBS [ 35 ], and DMAc for cementitious composites, were conducted, but this aspect is not yet well researched.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Randhawa et alet al [26] investigated the effect of surfactant concentration on dispersion and functionalization using Triton X-100 and suggested better functionalization of CNTs with COOH after dispersion, the optimum surfactant being 1.3 wt%. Various researches have suggested that there should be an optimum surfactant to MWCNTs ratio for the most efficient dispersion [27][28][29]. Konsta-Gdoutas et alet al [29] state that a weight ratio of surfactant to MWCNTs close to 4 is required for effective dispersion of nanotubes.…”
Section: Introductionmentioning
confidence: 99%